2021
DOI: 10.1093/cje/beab039
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exchange rate and structural change: an approach based on income elasticities of trade

Abstract: We analyse the hypothesis that variations in the income elasticities of the demand for exports and imports are influenced by the difference between the actual and industrial equilibrium levels of real effective exchange rates. The industrial equilibrium is defined as the exchange rate level that equalises real unit labour costs between local producers of manufactured goods and their trading partners. To test our hypothesis, based on data between 1995 and 2014 from the World Input-Output Database (WIOD), a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…So, Hypothesis 4 is supported only for skilled‐labour‐intensive industries. Many observers, including Nassif et al (2020), Bresser‐Pereira (2021), and Marconi et al (2021), expressed concern that the overvalued exchanged rate in Brazil during the 1990s may have shrunk the tradable sector and expanded the non‐tradable sector through reallocation of unskilled labour. This would lead to reductions of sectoral and aggregate labour productivity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…So, Hypothesis 4 is supported only for skilled‐labour‐intensive industries. Many observers, including Nassif et al (2020), Bresser‐Pereira (2021), and Marconi et al (2021), expressed concern that the overvalued exchanged rate in Brazil during the 1990s may have shrunk the tradable sector and expanded the non‐tradable sector through reallocation of unskilled labour. This would lead to reductions of sectoral and aggregate labour productivity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a policy‐induced depreciation in the level of the internal real exchange rate, defined as a rise in the domestic price of tradables ( P T ) relative to the domestic price of non‐tradables ( P N ), could relax the balance‐of‐payments constraint on demand growth. In this context, it is informative to examine some of the theoretical extensions to the canonical BPC growth model that have endogenised the relative income elasticities ( ε / π ) in Equation () to a one‐off change in the level of the real exchange rate (Cimoli et al., 2019; Marconi et al., 2021; Missio et al., 2017; Missio & Jayme, 2012; Setterfield & Ozcelik, 2018).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The methodology for estimating the IEER has been developed by Marconi (2012) that calculated the IEER for Brazil from 1988 to 2011. Recently, Marconi et al (2021) estimated the IEER for 43 countries and empirically tested its influence on the process of structural change. A simple way to calculate the IEER corresponds to the estimation of the exchange rate that compensates the differential between unit labor costs in the country and its competing trade partners in the domestic and foreign markets 6 .…”
Section: The Industrial Equilibrium Exchange Ratementioning
confidence: 99%
“…The importance of maintaining a competitive exchange rate has gained attention in the economic development debate over the last decades, and recent studies have found robust indications that a competitive exchange rate is determinant for stimulating investment, structural change, and economic growth (Ferrari, Freitas, Barbosa Filho, 2013;Gala, 2008;Guzman, Ocampo, Stiglitz, 2018;Marconi et al, 2021;Missio et al, 2015;Rapetti, Skott, Razmi, 2012;Rodrik, 2008). This emerging body of empirical evidence is accompanied by many studies that aim to understand that relationship at a more disaggregated level, arguing that there are important differences among the economic sectors that would engender diverse responses of the economic actors to an exchange rate appreciation or depreciation.…”
Section: Introductionmentioning
confidence: 99%